PENGEMBANGAN KREATIF POTENSI ALAM DESA SESAOT MELALUI WORKSHOP ECOPRINT - Safitri, Nurmayanggi Aulia; Alfarizi, Alfarizi; Amelia, Annisa Putri; Prameswari, Dinda Febyan; Ramdhan, Ilham; Hakim , Mia Safira; Hapsari, Mufidatul Ghina; Al Qodri, Mustofa; Sajiman, Rifki Rahardian; Azuandira, Septiawan; Maharani, Thahira Adela (Universitas Mataram, 2023)
Sesaot Village is a village that has abundant natural resources and can be used as a business opportunity from the abundance of natural resources in Sesaot Village, but entrepreneurship development in Sesaot Village is still relatively minimal, meaning that the many natural potentials that can be processed into a product are not matched by further development initiatives. This is based on the lack of education and knowledge of the local community in making and producing a product that has economic value. Therefore, it is necessary to carry out ecoprint workshops that add skills and knowledge in processing the potential of natural resources in Sesaot village and can become an innovative and creative business idea for the community. To achieve this goal, activities are carried out by delivering material and direct practice. As a result of a series of activities that have been carried out, the community is able to process the potential of natural resources in Sesaot village into an innovative and creative product using the ecoprint technique.